Permeability Evolution and Frictional Stability of Fabricated Fractures With Specified Roughness. Issue 11 (5th November 2018) - Fang, Yi; Elsworth, Derek; Ishibashi, Takuya; Zhang, Fengshou
Abstract: Roughness is widely observed on natural fractures, and its impact on the potential for induced seismicity and associated fluid migration in the subsurface remains unclear. Here we perform fracture shearing and fluid flow experiments on artificially fabricated fractures with specified roughness to investigate the role of fracture roughness on frictional properties and permeability evolution. Given the experimental conditions, we observe that rough fractures show high roughness ratio S q / L w and return higher frictional strength due to the presence of cohesive interlocking asperities. Rough fracture surfaces show velocity strengthening behavior in the initial shearing stage, which may evolve to velocity neutral and velocity weakening at greater displacements—suggesting a dynamic weakening that rough fractures become less stable with shearing. The surface roughness exerts a dominant control on permeability evolution over the entire shearing history. Permeability declines monotonically by about 2 orders of magnitude for smooth fractures. For high roughness fractures, the permeabilities evolve episodically due to cycled compaction and dilation during shearing. With a slip distance of 6 to 8 mm, permeability of the rough surface may enhance up to an order of magnitude, but significant permeability reduction may also occur for rough samples when asperities are highly worn with gouge clogging flow paths. However, there is no obvious correlation between permeability evolution and frictional behavior for rough fracture samples when fractures are subject to sudden sliding velocity changes. Key Points: Friction‐permeability relationships are investigated for fractures fabricated with controlled roughness amplitude and wavelength Roughness patterns of fracture exert a strong control on permeability evolution via alternating compaction and dilation during shearing Rough fractures show high frictional stability initially and stability decreases with shearing, suggesting an aseismic to seismic transition